Dacron Mesh witih Appendage: (Nylon Zipper) - Badano Repetto, José L; Badano Carbajal, José L (Cirugía del Uruguay, 1981)
Presentation of experimental work which shows the feasibility of employing a dacron mesh with zipper added, in a Iaparotomy. By this procedure, the abdomen was opened and closed 6 times on different dates. Tollerance was very good. Zipper resection was made when it was decided to end experiment. The author suggests that it might be used in human beings in particular circunstances.